Marinaleda : huelga de hambre contra el hambre / Candi Martínez, Gogofredo Camacho - Camacho, GodofredoSánchez Gordillo, Juan Manuel; Martínez, Candi (Nuestra Lucha ; 3)
Contiene entrevista a Juan Manuel Sánchez Gordillo